CRISTA-NF measurements with unprecedented vertical resolution during the RECONCILE aircraft campaign - Ungermann, J.; Kalicinsky, C.; Ulanovsky, A.; Ravegnani, F.; Weigel, K.; Stroh, F.; Riese, M.; Olschewski, F.; Knieling, P.; Hoffmann, L.; Blank, J.; Woiwode, W.; et al. (Atmospheric Measurement Techniques, 2012)
The Cryogenic Infrared Spectrometers and Telescope for the Atmosphere - New Frontiers (CRISTA-NF), an airborne infrared limb-sounder, was operated aboard the high-flying Russian research aircraft M55-Geophysica during the Arctic RECONCILE campaign from January to March 2010. This paper describes the calibration process of the instrument and the retrieval algorithm employed and then proceeds to present retrieved trace gas volume mixing ratio cross-sections for one specific flight in this campaign. We are able to resolve the uppermost troposphere/lower stratosphere for several trace gas species for several kilometres below the flight altitude (16 to 19 km) with an unprecedented vertical resolution of 400 to 500 m for the limb-sounding technique. The instrument points sideways with respect to the flight direction. Therefore, the observations are also characterised by a rather high horizontal sampling along the flight track, which provides a full vertical profile every approximate to 15 km. Assembling the vertical trace gas profiles derived from CRISTA-NF measurements to cross-sections shows filaments of vortex and extra-vortex air masses in the vicinity of the polar vortex.During this campaign, the M55-Geophysica carried further instruments enabling trace gas volume mixing ratios derived from CRISTA-NF to be validated by comparing them with measurements by the in situ instruments HAGAR and FOZAN and observations by MIPAS-STR. This validation suggests that the retrieved trace gas volume mixing ratios are both qualitatively and quantitatively reliable.